Evaluation for SARS-CoV-2 in Breast Milk From 18 Infected Women. Issue 3 (25th September 2021) - Chambers, C.; Krogstad, P.; Bertrand, K.; Contreras, D.; Tobin, N.H.; Bode, L.; Aldrovandi, G.
Abstract : ( JAMA . 2020;324:1347) While the concern that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may be transmitted to infants via breastfeeding has been raised, organizations recommend women infected with SARS-CoV-2 may continue to breastfeed if they so choose. There had been no documented cases of transmission of the virus to the infant through breast milk and to date the virus has not been directly isolated from breast milk.